AKTIFITAS ETNOMATEMATIKA PADA KONSEP RUMAH ADAT BUBUNGAN TINGGI DI BANJARMASIN TAHUN 2021/2022 - Muhammad Amin Paris; Said Salman Wahyuda (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the philosophical meaning of the design of the Banjar traditional house and to describe the design of the Banjar traditional house in an Ethnomatematics perspective in terms of Ethnomatematics activities and Mathematical concepts. This research focuses on the philosophy of the Banjar traditional house in ethnomathematics activities in the form of counting activities, location determination activities, and design activities as well as various mathematical concepts covering aspects of geometric studies in the form of two-dimensional geometry and three-dimensional geometry. This research is a type of qualitative research, in which data analysis does not use statistical analysis, but more narratively and the approach used in this research is an ethnographic approach. The subjects in this study are referred to as resource persons or historians from the Banjar traditional house who have an understanding of the history and form of the Banjar traditional house which can be studied using ethnomathematics. While the object of this study is the Banjar Bubungan Tinggi Traditional House. The data collected can be descriptive in the form of words or pictures. Data can be obtained from interviews, field observation notes, photographs, archive sources, personal documents and official documents. After the data has been collected, an analysis of the results of interviews, observations, and documentation is then followed by checking the validity of the data. Based on the results of the research, it can be concluded that parts of the Banjar Bubungan Tinggi traditional house have a deep philosophical meaning related to the life of the Banjarmasin people, both relations with humans and with the creator